1935
DOI: 10.1084/jem.61.6.839
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Suprarenal Cortex

Abstract: A number of papers during the past few years, particularly those of Stewart and Rogoff (1), of Marine and Baumann (2), and of Loeb and his coworkers (3), have shown clearly the close relations which exist between the suprarenal glands and the metabolism of salt and water. The recent studies of Loeb are of fundamental interest since they provide for the first time a rational explanation of the mechanism of suprarenal insufficiency, which this author suggests may be due to a primary loss of sodium through the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1935
1935
1941
1941

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…It will be seen from Figure 1, that, in a dog maintained on moderate doses of cortical extract, a decrease in blood sodium and an increase in blood urea could be induced either by the withdrawal of salt from the diet, by the gradual reduction of the dosage of cortical extract or by its complete withdrawal, as has been observed by Harrop (2,3). These changes in blood sodium and in blood urea, whether they followed the withdrawal of salt or the withdrawal of cortical extract, were accompanied by a progressive fall in the phthalein excretion and in urea clearance.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…It will be seen from Figure 1, that, in a dog maintained on moderate doses of cortical extract, a decrease in blood sodium and an increase in blood urea could be induced either by the withdrawal of salt from the diet, by the gradual reduction of the dosage of cortical extract or by its complete withdrawal, as has been observed by Harrop (2,3). These changes in blood sodium and in blood urea, whether they followed the withdrawal of salt or the withdrawal of cortical extract, were accompanied by a progressive fall in the phthalein excretion and in urea clearance.…”
Section: Resultsmentioning
confidence: 69%
“…The influence of the adrenal cortex upon electrolyte physiology and renal function has been the subject of many recent investigations (1,2,3). Improvement in the preparation of cortical extract has been advanced to a state where it is now possible to maintain experimental animals in perfect health indefinitely under the standard conditions of metabolism experiments.…”
mentioning
confidence: 99%
“…from other channels than urine. 4 In Table IIIC 62.1 m.eq. of sodium per day from other channels than urine.…”
Section: Methodsmentioning
confidence: 99%
“…(Received for publication August 18, 1938) The efficacy of sodium salts in the treatment of adrenal cortical insufficiency in man and experimental animals has been recognized, and the changes in the distribution and excretion of water and electrolytes following their therapeutic use have been investigated (1,2,3,4). This present study is concerned with the effect of variations in the total water consumption of a patient with Addison's disease receiving a relatively constant high intake of sodium chloride.…”
Section: Philadelphia)mentioning
confidence: 99%
“…4 during adrenal insufficiency indicates, as was suggested in our earlier paper (5), that the changes in electrolyte and nitrogen balance found during moderately advanced adrenal insufficiency are in a measure dependent upon the lowered food consumption after adrenalectomy. Harrop and his associates (14) have shown that the lowered blood sugar found during adrenal insufficiency in dogs is dependent upon the lowered food intake. However, it is apparent from our data that the lowered food intake is not the entire cause of the altered balances, for the reduced retentions of sodium, potassium, and chlorine during adrenal insufficiency are greater than those seen in similar degrees of undernutrition in normal rats.…”
Section: I I 690mentioning
confidence: 99%